Design and Build a Ventalitor Tester With PIP and PIF Waveform Displays As Validation (PIP) - Sandhi Dhanindra; Her Gumiwang Ariswati; Dyah Titisari; Mansour Asghari (Jurnal Teknokes, 2023)
PIP (Peak Inspiratory Pressure) is the highest level of pressure exerted into the lungs by the ventilator during inhalation. This PIP parameter is important for monitoring because inappropriate PIP values ​​can lead to fatal errors in patients. PIP should be kept below 20 to 25 cm H2O each time ventilation. This PIP control can be a value as well as a waveform. This waveform display is also used to validate the ventilator output. Checking the output on this ventilator is used using a ventilator tester. The purpose of this research is to get the accuracy and precision of the sensor to display the waveform and PIP value of the ventilator output. The procedure of this research is to use MPX5010GP to detect the pressure value on the ventilator and then display the value and waveform of the PIP. From this study, the results of the measurement of accuracy and precision from the MPX5010 sensor to detect PIP and display a waveform graph are said to be good. This is because the highest error value is ±6.27% at the 15 CmH20 setting. While the value of the largest standard deviation at the 15 CmH20 setting is 0.837 and the greatest uncertainty value at the 15 CmH20 setting is 0.033. Then, the largest correction value is found in the 25 CmH20 setting, which is 1.56. PIF monitoring is carried out to maximize service to patients and maximize ventilator care.